Factors affecting English language teachers’ behavioral Intentions to teach online under the pandemic normalization of COVID-19 in China - Gao, Yanjun; Wong, Su Luan; Md. Khambari, Mas Nida; Noordin, Nooreen; Geng, Jingxin; Bai, Yun (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The unexpected outbreak of COVID-19 pandemic forced most teachers across the globe to switch their teaching from traditional face-to-face to online without having received adequate preparation and knowledge related to online teaching. To better comprehend teachers’ willingness to conduct emergency remote teaching during the worldwide crisis, the current study was designed to examine teachers’ intentions and, in particular, the factors affecting their behavioral intentions to teach online, by contextualizing the research in the English language teaching settings in China. The research model was developed based on an extended technology acceptance model (TAM) by adding subjective norm, self-efficacy, technological complexity, and facilitating conditions into the original TAM. The data were obtained from a total of 287 respondents including 228 (79.4%) female teachers and 59 (20.6%) male teachers via online questionnaires. The questionnaire was developed by adapting previously validated instruments and then refined by two educational technology experts in order to better suit the current study. The empirical findings, using structural equation modeling (SEM), showed that the extended TAM was valid in predicting English language teachers’ intentions to teach online during the pandemic normalization. At the same time, the findings suggested that teachers’ intentions were influenced significantly by attitude, facilitating conditions, and self-efficacy; language teachers’ attitude toward online teaching was significantly affected by both its perceived usefulness and perceived ease of use; perceived usefulness had a significant association with perceived ease of use and subjective norms; and perceived ease of use was significantly impacted by self-efficacy and facilitating conditions. Perceived usefulness was not suggested as a significant determinant of English language teachers’ intentions to adopt online teaching. Despite some limitations, the study has several implications from the perspective of theory and practice. The more factors with a higher influence should be determined from different perspectives in future research.